Pengaruh Return On Equity Dan Return On Asset Terhadap Harga Saham Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia - Gaffar, M.Arqam; Mus, Abdul Rahman; Suriyanti, Suriyanti; Mahmud, Amir (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to: (1) investigate the influence of Return on Equity (ROE) on the stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange (ISE) during the period 2018-2022; and (2) examine the impact of Return on Assets (ROA) on the stock prices of pharmaceutical companies listed on the ISE over the same period. The research employs a quantitative approach, utilizing secondary data derived from company annual reports, books, journals, and other pertinent documents related to the pharmaceutical industry. The primary data source consists of the annual financial statements of pharmaceutical companies listed on the Indonesia Stock Exchange. The data analysis is conducted using the Statistical Product and Service Solutions (SPSS) software, ensuring a rigorous statistical examination of the variables. The results of this study reveal that: (1) Return on Equity exerts a positive, albeit not statistically significant, effect on the stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange during the 2018-2022 period; and (2) Return on Assets exerts a negative, though not statistically significant, impact on the stock prices of these companies during the same period. These findings suggest that a higher Return on Equity is generally associated with an increase in stock prices, indicating that investors perceive a high ROE as a signal of a company's efficiency in generating profits from shareholders' equity. In contrast, a higher Return on Assets appears to correlate with a decrease in stock prices, implying that a lower ROA may indicate inefficiencies in the company's use of its assets to generate profits. Based on these insights, the study recommends the following: (1) Management should focus on improving ROA by optimizing asset utilization to enhance profitability. (2) Pharmaceutical companies listed on the Indonesia Stock Exchange should strive to improve their financial performance in subsequent years, with an emphasis on generating higher profitability as reflected in their financial statements. Keywords: ROE, ROA, Stock Prices, Pharmaceutical Companies